A participatory model through project-based learning in natural moringa oleifera soap production - Nurul Febriani Putri; Fitri Handayani; Fitriagustiani Fitriagustiani; Muh. Chaeril Ikramullah; Pasmawati Pasmawati; Muh. Rizqy Firmansyah; Naziiha Maitsa (Universitas Pendidikan Indonesia, 2025)
The widespread use of conventional soaps containing synthetic chemicals often poses risks of skin irritation and environmental pollution, necessitating the development of natural alternatives, such as soaps based on Moringa oleifera and Virgin Coconut Oil (VCO). At MAN 2 Parepare, abundant local resources remain underutilized due to the lack of integration of applied biotechnology into a predominantly theoretical curriculum. This community service program aimed to enhance students' competence in formulating natural soap using the cold process method through a Project-Based Learning (PjBL) approach. The implementation employed a participatory Service Learning method involving science students, encompassing saponification theory lectures, technical formulation training, and effectiveness evaluation through testing instruments. The results indicated a significant increase in cognitive and psychomotor competence, marked by a substantial improvement in participants' post-training understanding and high learning effectiveness. Beyond successfully creating eco-friendly antibacterial soap bars, the intervention substantially boosted participants' soft skills and entrepreneurial interest. It is concluded that PjBL effectively bridges the gap between biotechnology theory and practice and transforms students' knowledge into productive, economically valuable skills. The program recommends establishing a school entrepreneurship unit and further standardizing products to ensure the sustainability of educational impacts and economic empowerment grounded in local wisdom. Abstrak Sabun konvensional berbahan kimia sintetik sering kali menimbulkan risiko iritasi kulit dan pencemaran lingkungan, sehingga mendorong urgensi pengembangan alternatif alami seperti sabun berbasis Moringa oleifera dan Virgin Coconut Oil (VCO). Di MAN 2 Parepare, potensi sumber daya alam lokal yang melimpah belum dimanfaatkan secara optimal karena kurangnya integrasi bioteknologi terapan dalam kurikulum sekolah yang masih didominasi teori. Program pengabdian ini bertujuan meningkatkan kompetensi murid dalam memformulasi sabun natural menggunakan metode cold process melalui pendekatan Project-Based Learning (PjBL). Metode pelaksanaan menerapkan Service Learning partisipatif yang melibatkan murid jurusan IPA, mencakup tahapan penyuluhan teori reaksi saponifikasi, pelatihan teknis formulasi, dan evaluasi efektivitas melalui instrumen tes. Hasil kegiatan menunjukkan lonjakan kompetensi kognitif dan psikomotorik yang signifikan, ditandai dengan peningkatan drastis pemahaman peserta pasca-pelatihan serta capaian efektivitas pembelajaran yang masuk dalam kategori tinggi. Selain berhasil menciptakan produk sabun padat antibakteri yang ramah lingkungan, intervensi ini terbukti meningkatkan soft skills dan minat wirausaha peserta secara substansial. Disimpulkan bahwa integrasi PjBL efektif menjembatani kesenjangan antara teori dan praktik bioteknologi, sekaligus mentransformasi pengetahuan murid menjadi keterampilan produktif bernilai ekonomi. Program ini merekomendasikan inisiasi unit kewirausahaan sekolah dan pendampingan standardisasi produk lanjutan guna menjamin keberlanjutan dampak edukatif serta pemberdayaan ekonomi komunitas sekolah berbasis kearifan lokal. Kata Kunci: bioteknologi; Moringa oleifera; pembelajaran berbasis proyek; proses dingin; sabun alami